Control of the ethylene signaling pathway prevents plant defenses during intracellular accommodation of the rhizobia. Issue 1 (18th April 2018) - Berrabah, Fathi; Balliau, Thierry; Aït‐Salem, El Hosseyn; George, Jeoffrey; Zivy, Michel; Ratet, Pascal; Gourion, Benjamin
Summary: Massive intracellular populations of symbiotic bacteria, referred to as rhizobia, are housed in legume root nodules. Little is known about the mechanisms preventing the development of defense in these organs although genes such as SymCRK and DNF2 of the model legume Medicago truncatula are required for this control after rhizobial internalization in host nodule cells. Here we investigated the molecular basis of the symbiotic control of immunity. Proteomic analysis was performed to compare functional (wild‐type) and defending nodules ( symCRK ). Based on the results, the control of plant immunity during the functional step of the symbiosis was further investigated by biochemical and pharmacological approaches as well as by transcript and histology analysis. Ethylene was identified as a potential signal inducing plant defenses in symCRK nodules. Involvement of this phytohormone in symCRK and dnf2 ‐developed defenses and in the death of intracellular rhizobia was confirmed. This negative effect of ethylene depended on the M. truncatula sickle gene and was also observed in the legume Lotus japonicus . Together, these data indicate that prevention of ethylene‐triggered defenses is crucial for the persistence of endosymbiosis and that the DNF2 and SymCRK genes are required for this process.